Sirukam Dairy Farm Agrotourism Development Model in Solok Regency - Nelvi, Yusmi; Yora, Muharama (Journal of Animal Nutrition and Production Science, 2023)
Basically, agrotourism is placing the primary sector (agricultural sector) in the tertiary sector (tourism sector) which aims to help increase farmers' income. Farmers and the agricultural sector will benefit from agrotourism activities. Agrotourism can maintain the sustainability of the agricultural sector and prevent the agricultural sector from being marginalized. There are many reasons why tourists are interested in seeing the beauty of nature and carrying out various activities in the open air, including enjoying the beauty that agrotourism provides. A number of areas in Solok Regency are currently being developed as agrotourism areas, one of which is Sirukam Dary Farm, but this agrotourism management model is very different from the others. The diversity of agrotourism management models becomes material for study to develop agrotourism development models that apply in different conditions at these agrotourism objects. This article explains in detail the agrotourism development model at Sirukam Dairy Farm and it is hoped that it can be used for agrotourism management in other regions throughout Indonesia.